Standard operating procedures for re-establishing dental services in an acute NHS trust following COVID-19 - Rasaratnam, Lakshmi; Elder, Andrew; Parker, Donna (Faculty dental journal, 2020)
As consultants in restorative dentistry working within an acute NHS trust, our role primarily involves working as part of a multidisciplinary head and neck service alongside our orthodontics and maxillofacial colleagues to provide treatment for patients with head and neck cancer, cleft lip and palate, hypodontia, and dentoalveolar and facial trauma. In March 2020, the provision of these essential services was brought to an abrupt halt; with the exception of urgent head and neck cancer care, due to the COVID-19 pandemic. This virus not only impacted how we lived our lives but how we provided key services in hospital dentistry. This article provides clear guidance on personal protective equipment (PPE), infection prevention and control guidance; the role of amber cleans and the integration of laboratory services into safe working environments. We understand that the standard operating procedures in this article are accurate at the time of publication but may be subject to change due to updated government guidelines. Managing risks and alleviating concern: new protocols for patient and staff safety.